2023
DOI: 10.1111/jre.13125
|View full text |Cite
|
Sign up to set email alerts
|

Salivary E‐cadherin as a biomarker for diagnosis and predicting grade of periodontitis

Abstract: Objectives To determine the abilities of salivary E‐cadherin to differentiate between periodontal health and periodontitis and to discriminate grades of periodontitis. Background E‐cadherin is the main protein responsible for maintaining the integrity of epithelial‐barrier function. Disintegration of this protein is one of the events associated with the destructive forms of periodontal disease leading to increase concentration of E‐cadherin in the oral biofluids. Materials and Methods A total of 63 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Indeed, the level of soluble E-cadherin in saliva of periodontitis patients has also been found to be significantly higher than in healthy counterparts. 21,22 Consistently, this work demonstrated that the level of GCF E-cadherin significantly reduced after treatment and following the restoration of the healthy state of the periodontium.…”
Section: Ta B L Esupporting
confidence: 74%
See 4 more Smart Citations
“…Indeed, the level of soluble E-cadherin in saliva of periodontitis patients has also been found to be significantly higher than in healthy counterparts. 21,22 Consistently, this work demonstrated that the level of GCF E-cadherin significantly reduced after treatment and following the restoration of the healthy state of the periodontium.…”
Section: Ta B L Esupporting
confidence: 74%
“…Destruction of AJs and the release of the unbounded E‐cadherin due to proteolytic cleavage is evident in a range of inflammatory diseases 18–20 . Consistent with this observation, the level of soluble E‐cadherin in salivary samples of periodontitis patients was found to be significantly higher than in healthy controls 21,22 . Furthermore, immunohistochemical analysis of periodontally diseased tissue samples demonstrated reduced E‐cadherin levels 16 …”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations